MAKNA DAN MAJAS DALAM IDIOM (KANYOUKU) YANG BERUNSUR MATA (ME目) DAN MULUT (KUCHI 口) - Larasati, Kinanti (Japanese Literature, 2013)
In Japanese language, to express feelings, ideas, and opinions, can use kanyouku. Kanyouku is formed by two or more word elements, which harmoniously merge into a specific meaning. Kanyouku cannot be interpreted as lexical or grammatical, but it can only be explained by idiomatical meaning. This study aims to classify the meaning of kanyouku me and kuchi based on the construction pattern of kanyouku me and kuchi, seek the extension meaning of kanyouku me and kuchi, and analyze the classification of Idiomatical meaning of kanyouku me and kuchi. The method used in this thesis is descriptive analysis and divided into three phases, namely data collection, data analysis, and final presentation of data analysis in conclusions. The books used in this thesis are Reikai Kanyouku Jiten and Idiom Bahasa Jepang Memakai Nama-nama Bagian Tubuh. Kanyouku which is studied in this thesis amounted to twenty eight pieces, consisting of thirteen pieces of doushi kanyouku, eight pieces of keiyoudoushi kanyouku, and seven pieces of meishi kanyouku. Nevertheless, It can be concluded that there are five pieces of kanyouku showing feelings or emotions, ten pieces of kanyouku associated with the body, character, and attitude, six kanyouku that shows action, activity, or action, six pieces of kanyouku indicate a state, degree, or grade level, and a piece of kanyouku showing the life, culture, and the local community. From the research, it can be said that twenty eight kanyouku has studied using the metaphorical, metonym, and synekdoche extension of meaning. Keywords : Kanyouku, Me, Kuchi, Metaphor, Metonym, Synekdoche